2013
DOI: 10.4014/jmb.1306.06026
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus sakei Lipoteichoic Acid Inhibits MMP-1 Induced by UVA in Normal Dermal Fibroblasts of Human

Abstract: Human skin is continuously exposed to ultraviolet (UV)-induced photoaging. UVA increases the activity of MMP-1 in dermal fibroblasts through mitogen-activated protein kinase (MAPK), p38, signaling. The irradiation of keratinocytes by UVA results in the secretion of the inflammatory cytokine, tumor necrosis factor-α (TNF-α), and the stimulation of MMP-1 in normal human dermal fibroblasts (NHDFs). Lipoteichoic acid (LTA) is a component of the cell wall of gram-positive Lactobacillus spp. of bacteria. LTA is well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…Commensal bacteria lipoteichoic acid increases skin mast cell antimicrobial activity against vaccinia viruses (Wang et al, 2012). In the previous study we have shown that sLTA isolated from Lactobacillus sakei inhibited UVA-induced MMP-1 through the inhibition of MAPK/JNK signaling in human dermal fibroblasts (You et al, 2013). In addition, LTA from S. aureus (aLTA) reduced iNOS expression and NO production in the mouse model of renal ischemia reperfusion injury (Chatterjee et al, 2002).…”
Section: Discussionmentioning
confidence: 97%
“…Commensal bacteria lipoteichoic acid increases skin mast cell antimicrobial activity against vaccinia viruses (Wang et al, 2012). In the previous study we have shown that sLTA isolated from Lactobacillus sakei inhibited UVA-induced MMP-1 through the inhibition of MAPK/JNK signaling in human dermal fibroblasts (You et al, 2013). In addition, LTA from S. aureus (aLTA) reduced iNOS expression and NO production in the mouse model of renal ischemia reperfusion injury (Chatterjee et al, 2002).…”
Section: Discussionmentioning
confidence: 97%
“…Probiotics mainly act in the gut and exhibit various beneficial effects via improvement of the gut environment. By contrast, some components of lactic acid bacterial bodies are known to have direct effects on the host, for example, extracellular polysaccharide, lipoteichoic acid, and peptidoglycan . These substances are called biogenics and viable bacteria are not required for their effects .…”
Section: Discussionmentioning
confidence: 99%
“…For example, the bacterial products or the components of bacterial bodies can act as biologically active substances. In this case, it is not necessary that living bacteria exist in the host [26, 27]. It has been reported that heat-killed Lactobacillus rhamnosus GG (LGG) showed anti-inflammatory effects as well as living LGG, and some bacterial components of heat-killed LGG have been shown to be effective [28].…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that some active substances likely contributed to the anti-oxidative effects of LG2055. Many functional effects of the substances derived from bacterial bodies have been studied and the effects of extracellular polysaccharide [40], lipoteichoic acid [26], and peptidoglycan [41] have been reported. As it is known that the structures of bacterial components differ between species or strains of the bacteria, it is expected that the differences in the functions of several lactic acid bacteria might be caused by structural differences between species or strains [42].…”
Section: Discussionmentioning
confidence: 99%